Synthesis and evaluation of the effect of structural parameters on recovery rate of shape memory polyurethane-POSS nanocomposites. (May 2019) - Kazemi, Forouzan; Mir Mohamad Sadeghi, Gity; Kazemi, Hamid Reza
Graphical abstract: Increase crystallinity in soft domains. Highlights: New method to synthesize nanocomposite POSS-PU. Improvement the crystallinity of soft segments by adding nanoparticles in the polyurethane matrix. POSS nanoparticles increase the storage modulus. Adding nanoparticles has led to improvement the recovery rate, shape recovery, explosive reversibility. Abstract: Recovery rate and recovery stress are important factors that limit the use of polyurethanes, especially in the medical field. In this study, Polyhedral Oligomeric Silsesquioxane nanoparticles as chain extender have been bonded to polyurethane chains using a new synthesis method. Fourier-transform infrared spectroscopy technique to confirm synthesis reactions, Differential Scanning Calorimetry for evaluating the effect of Polyhedral Oligomeric Silsesquioxane (POSS) particles on the crystallinity of soft segments, Dynamic Mechanical Thermal Analysis for investigating mechanical properties, and Scanning Electron Microscope and X-ray diffraction have been used to evaluate the dispersion of Nanoparticles, respectively. It is observed that using Polyhedral Oligomeric Silsesquioxane solely, acts as a chain extender which does not show phase separation in synthesized nanocomposites. Using both the Polyhedral Oligomeric Silsesquioxane and 1, 4-Butanediol chain extender in polyurethane synthesis reaction caused greater phase separation rather than solely 1, 4-Butanediol. Finally, adding the nanoparticles caused improvement in recovery rate as well as shape recovery in the synthesized nanocomposites.